Rotary Electrical Controlled Drum Dryer for Organic Fertilizer Production - Naswir Naswir; Elvin Hasman; A Irwan (Politeknik Pertanian Negeri Payakumbuh, 2019)
this research is aim to provide design and prototype of rotary electrical controled drumdrier machine for drying organic fertilizer to increased production capacity and quality by using a source of heat energy from electricity. This machine consists of five main components i.e. drying cylinder, heating unit, support frame, engine and transmission system. Engine specifications are high 130 cm, 720 cm long, and 120 cm wide, cylinder diameter 60 cm, power engine 14 hp, and heating temperature 142 oC. engine performance test are: capasity 805,03 kg/hours, drying rate 27,40 %/hours, noise level 81,54 db. cost analysis result are operational cost 155,06 Rp/kg and Break Event Point 159.219,73 kg/years